Aplikasi Menu Restoran Sushi Jepang Menggunakan Augmented Reality (AR) - Yesmaya, Violitta; Devin, Devin; Roesli, Aldo Biondy; Primaguna, Radik (Yayasan Petra Harapan Bangsa, 2019)
The development of technology is now increasingly rapid. This can be proven from the many applications that make it easier for users to carry out their daily activities. Many restaurants offer food menus, but not all food menus are visualized on the menu book. This makes the customers always ask back to the staff about the menus from the restaurant. From these problems, research is made that can facilitate users in ordering food displayed in 3D, so that the appearance of the food menu is more clear and attractive to users. The method used in this study is the waterfall method where the application development is carried out systematically. The waterfall method has several steps that must be followed: requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results of the study are